The Use of Modulation in Translating Metaphors from English to Indonesian in L.M. Montgomery’s The Golden Road - Farah Fatihah; Cholsy, Hayatul (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2025)
This study aims to identify and analyze the modulation used in translating metaphors in L.M. Montgomery’s The Golden Road using the modulation classification theory proposed by Vinay and Darbelnet. While previous studies on modulation mainly focus on equivalence and meaning shift, there is limited research exploring the specific role of modulation method in translating metaphors, especially in literary works. To address this gap, this study utilizes a descriptive-comparative qualitative method, the data for this study are metaphorical expressions translated with modulation from the English novel The Golden Road and its translation into Indonesian titled Hari-Hari Bahagia by L.M. Montgomery. The result of this study reveals that out of 181 data, 6 out of 10 types of modulation applied by the translator in this novel are explicative modulation (51%), abstract for concrete (23%), change of symbols (20%), negation of the opposite (3%), active to passive (vice versa) (2%), and one part for another (1%). This study shows that metaphor translation not only focuses on word equivalence but also requires creativity and a deep understanding of both languages to maintain the essence and uniqueness of the source text.